English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-06-18 13:10:50 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

(c-9)(c+3)

2007-06-18 13:13:09 · answer #1 · answered by ironduke8159 7 · 0 0

You must learn the procedure

to factor a function like y = ax^2 +bx+c

1) first find the roots x1 and x2
2) put in the form: y = a(x-x1)(x-x2)

In your case: y = x^2 -6x -27

1) find the roots: x^2 -6x -27 =0 ==> x1= 9 and x2 =-3
2) put int the form: y = 1(x-9)(x-(-3)) = (x-9)(x+3)

You can now verify the result expanding the product.

2007-06-18 20:18:40 · answer #2 · answered by vahucel 6 · 0 0

c^2-6c-27
is of form ax^2+bx+c a=1 b=-6 c=-27
there are 2 solutions namely,
[-b+sqrt(b^2-4ac)]/2 and [-b+sqrt(b^2-4ac)]/2
-(-6)+sqrt(36-4(1)(-27))]/2
=6+sqrt(36+108)]/2
=[6+12]/2=9 (c+9)=0 or c=-9
the second solution
[-(-6)-sqrt(36+108))]/2
=[6-12]/2=-3 (c-3)=0 or c=3
(c-9)(c+3)

2007-06-18 20:19:53 · answer #3 · answered by cidyah 7 · 0 0

(c - 9) (c + 3)

2007-06-18 20:13:11 · answer #4 · answered by davemb78 2 · 0 0

fedest.com, questions and answers